Reproducibility of Task-Oriented Bimanual and Unimanual Strength Measurement in Children with Unilateral Cerebral Palsy. (4th July 2019) - Geijen, Mellanie; Rameckers, Eugene; Schnackers, Marlous; Bastiaenen, Carolien; Gordon, Andrew; Speth, Lucianne; Smeets, Rob
Abstract: Aim: To examine reproducibility of the arm-hand strength measured while performing the bimanual crate task and the unimanual pitcher task. Methods: 105 children diagnosed with unilateral Cerebral Palsy, aged between 6 and 18 years, participated in this study. The test–retest reliability of the force generated during bimanual crate task and unimanual pitcher task of the Task-oriented Arm-hAnd Capacity instrument was investigated using intraclass correlation two-way random model with absolute agreement. The intraclass correlations were calculated for two age groups (6–12 and 13–18 years old). Results: The results showed good test–retest reliability for the crate and pitcher task with the non-affected hand for both age groups. The results of the pitcher task for the affected hand showed moderate test–retest reliability for both age groups. Conclusion: The Task-oriented Arm-hAnd Capacity instrument has moderate to good test–retest reliability. It is a simple and objective instrument to assess task-oriented strength in children with unilateral cerebral palsy.